Analytical Study of MNREGA’s Impact on Rural Livelihood of Indian State of Assam - Anwar Hussain (The Indonesian Institute of Science and Technology Research, 2022)
MNREGA is one of the flagship programmes initiated by the government of India to enhance the livelihood of the rural poor by providing extensive employment opportunities. The Indian State of Assam comprises 3.63 crores of the population, of which approximately 86 per cent of the population lives in rural areas. The majority of them reside in the BPL category. The unemployment rate is also at its peak. Hence there is a question mark about the safety and security of these people. This Scheme will give a new direction to live a secure social life. The overall labour budget has to be reduced this year, yet innovative and extensive use of these funds will ensure the rural life of the people. This programme will bring a holistic change to the economy by providing supportive initiatives toward self-reliance, women empowerment, and poverty elevation.